Faktor-Faktor yang Menghambat Partisipasi Petani Subak Abian Sari Boga dalam Pengembangan Ekowisata di Banjar Kiadan, Desa Pelaga, Kecamatan Petang - I KADEK ARIANTA; I KETUT SURYA DIARTA; I MADE SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2015)
Abstract Factors that Inhibiting Participation of Subak Abian Sari Boga Member in Ecotourism Development at Kiadan Village, Petang District. World Tourism Organization (WTO), revealed there are some new developments in the world of tourism, namely the tendency of the global community to get back to nature. Thus the interest of tourists to travel to natural places become greater. This trend is the trigger for the development of tourism based on the natural environment. One of the villages that develop ecotourism in Bali is Kiadan village, which is located in Badung regency. Ecotourism in the village is in synergy with Subak Abian Kiadan. problem that appears is lack participation of subak member in the development of ecotourism. Purpose of this research is to determine the factors that hinder participation members of Subak in the development of ecotourism. Factor analysis method is used to answer the research objectives. The variables in this analysis include internal factors and external factors. Factor analysis generate four new factors with eigenvalue> 1. these four factors can explain 65.943% of the total variance parameters that affect the inhibition of Subak members' participation in the development of ecotourism. These four factors that hinder participation in the development of ecotourism Subak members, namely: (1) the distribution factor of information, communication, benefits and improving incomes; (2) social environmental factors, fulfilling the needs of households and benefits for farming; (3) the compatibility factor of kind of work and farm income; and (4) the location of ecotourism and exclusivity factor farmer involvement. Keywords: Participation, Farmer, Subak Abian, Ecotourism